23. FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN KERJASAMA INDONESIA DENGAN VIETNAM DALAM MENANGANI IUU FISHING - Putri, Anindia Cahya; Susiatiningsih, Hermini; Hanura, Marten (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
The increasing rate of fish consumption in the world has made some countries flocking tofulfill their needs of fish. In the process of fulfilling their needs of fish, they are doingeverything they can, both legally and illegally, in these case through Illegal UnreportedUnregulated Fishing. The act of these IUU fishing has caused a lot of damage and losses tothe affected countries and also could ruin the ecosystem of the affected sea. Indonesia as acountry with plenty of fish resources has became an appealing target for these act. One of theneighbouring countries who has been caught doing these act was Vietnam. To reduce thefrequencies of these illegal act and lessen the damages and losses, Indonesia cooperated withVietnam by making a Memorandum of Understanding or MOU. These cooperation betweenIndonesia and Vietnam ended with a good result, thankfully. This research was done in orderunderstand the factors of the successful cooperation against IUU fishing between Indonesiaand Vietnam. In accordance to achieve the goal of these research and solve the problem thatoccured, it was done by using theory of international cooperation, analyzing the indicators ofsuccess of the cooperation, concept theory of foreign policy and theory of cooperation inliberalis-paradigm, These research was done in qualitatif method with descriptic-analythicalway through journal research and interview. Results of the study are the success ofIndonesia's cooperation with Vietnam in dealing with IUU fishing due to the proximity offactor, communications, law enforcement.